Modelling Workplace Ostracism among Workforces amid Pandemic Outbreaks - Othman, Nor Azairiah Fatimah; Izhan, Farsha Farahana Ahmad; Sundram, Veera Pandiyan Kaliani; Majid, Muhammad; Mat Din, Syaidatul Zarina; Abdul Munir, Zarina; Mohamed Razali, Murni Zarina (Information Management and Business Review, 2023)
Amid pandemic outbreaks, many jobs that were once thought to be safe are now considered potentially harmful since the virus can be easily spread from one person to another. Albeit vaccination program, the fear of infections at the workplace is still alarming as getting vaccinated is a voluntary act and the virus keeps evolving from time to time. As everyone must keep their working life at risk since social distancing and wearing face masks are no longer being forcefully practiced, people are taking safety precautions into their own hands, leading to changes in ostracized behavior in the workplace. Following the Theory of Protection Motivation, this paper made attempts to conceptually model workplace ostracism to understand why some workforces are changing their behavior towards ostracism during a pandemic outbreak. Towards the end, the findings from this study are expected to contribute towards achieving mentally stable workforces and sustainable human resources.